Understanding the Role of School Management Committees (SMCs) in the Context of Effective Implementation of the Right to Education Act - 2009 - Singh, Pooja (THE PRIMARY TEACHER, 2012)
People’s participation is fundamental to the success of Sarva Shiksha Abhiyan (SSA) and for proper implementation of Right to Education Act (RTE). The objective of equitable quality for all children can be attained only with active participation of all stakeholders including parents, teachers, community, civil society and children. We have not been able to attain community support and implement effective strategies for community mobilization. It is required for translating RTE from a legal framework on paper to a vibrant movement on the ground. Local governance of education is not a new phenomenon in India after independence. Education is a subject in concurrent list. Under the concurrent list, the central government is expected to have a meaningful partnership with the state governments for educational development. Further, local self governments, viz. Panchayati Raj Institutions in rural areas, Municipalities in urban areas have been entrusted with the responsibility of education of children in order to make the system more decentralized and responsive to local requirement through community participation and ownership. However, the decentralization of educational management has not taken its shape and structure even after more than two decades for effecting desirable changes.